Production and fate of faecal pellets during summer in an East Antarctic fjord - Beaumont, KL; Plummer, AJ; Hosie, GW; Ritz, DA (2001)
The abundance of small faecal pellets is high in marine waters. Little is known, however, about the processes governing their production and fate in the water column. We investigated faecal pellet production and flux in relation to the phytoplankton and copepod assemblages present in Ellis Fjord, Antarctica. Results show that the phytoplankton community shifted from a dominance of diatoms to that of a cryptomonad species during late January. This coincided with an increase in abundance of the small copepods Paralabidocera antarctica and Oithona similis, although Oncaea curvata was still the dominant species. The mean faecal pellet flux was 9943 pellets m-2 d-1. Only 37% of the faecal pellet flux at 5 m sedimented to 10 m depth, 15% to 20 m, and 12% to 40 m depth. Our results suggest that recycling of faecal pellets by copepods contributes to this decreased flux with increasing depth, which concurs with results from large scale oceanic studies. Additionally, we propose that the summer ice melt changes the physical characteristics of the water column and the phytoplankton species abundance and distribution; both of which potentially impact on the distribution and abundance of copepods, thereby regulating faecal pellet flux.